2021
DOI: 10.1021/acs.jpclett.1c02492
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structural and Electronic Properties of TiSe2 under High Pressure

Abstract: A pressure-induced structural phase transition and its intimate link with the superconducting transition was studied for the first time in TiSe2 up to 40 GPa at room temperature using X-ray diffraction, transport measurement, and first-principles calculations. We demonstrate the occurrence of a first-order structural phase transition at 4 GPa from the standard trigonal structure (S.G.P3̅m1) to another trigonal structure (S-G-P3̅c1). Additionally, at 16 GPa, the P3̅c1 phase spontaneously transforms into a monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
1
19
2
1
Order By: Relevance
“…65 This sign inversion of the thermopower occurred in the pressure range in which earlier studies observed a transition to a superconducting state at low temperatures. 7,66 At B4-4.5 GPa, the thermopower curves inverted their slopes (the inset in Fig. 5).…”
Section: Resultsmentioning
confidence: 89%
“…65 This sign inversion of the thermopower occurred in the pressure range in which earlier studies observed a transition to a superconducting state at low temperatures. 7,66 At B4-4.5 GPa, the thermopower curves inverted their slopes (the inset in Fig. 5).…”
Section: Resultsmentioning
confidence: 89%
“…The pressure dependence of the electrical resistance of Sb 2 S 3 was determined by using the standard four-electrode method in a DAC. 49 The gasket was covered with an insulating layer of fine cubic boron nitride (cBN) powder, and thin platinum wires were used as electrodes. No PTM was loaded to avoid additional errors in the electrical measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The pressure dependence of the electrical resistance of Bi 2 Te 2 Se and Bi 2 Se 2 Te was determined using the standard four-electrode method in a DAC. 23 The gasket was covered with an insulating layer of fine cubic boron nitride ( c BN) powder, and thin platinum wires were used as electrodes. No PTM was loaded to avoid additional errors in the electrical measurements.…”
Section: Methodsmentioning
confidence: 99%